The Increase of HDL-C Levels using Ethanol Extract of Vernonia amygdalina Leaves in Wistar Rats Models of Metabolic Syndrome - Pakha, Dyonisa Nasirochmi; Nurwati, Ida; Sunggoro, Agus Jati; Muthmainah, Muthmainah; Handayani, Selfi (Smart Medical Journal, 2023)
Introduction: Metabolic syndrome (MetS) is a cluster of metabolic factors, including low high-density lipoprotein cholesterol (HDL-C) levels. Vernonia amygdalina (VA) leaves have been documented for their anti-cholesterol properties. The purpose of this study to evaluate ethanol extract of VA leaves in rising HDL-C levels in the MetS model.Methods: An experimental study using pre-and post-test design was conducted using 30 male Wistar rats divided into five groups randomly. KN group served as the control group. KP group was the MetS model without ethanol extract administration. Meanwhile, P1, P2, and P3 were MetS models and were administered ethanol extract of VA leaves administration (50mg/kg, 100mg/kg, and 150 mg/kg) for 28 days. The data were analysed using paired t-test and one-way ANOVA (α=0,05).Results: This study discovered that administering the extract in P1, P2, and P3 significantly improved HDL levels. Furthermore, increasing the dose resulted in significantly greater HDL levels. VA leaves contain phytochemicals that have impacts on cholesterol levels in the blood. Flavonoids and tannin inhibit ester cholesterol formation. Terpenoid and flavonoid hinder HMG-CoA. Saponin contributes to free cholesterol transporter, reducing oxidative stress and increasing LDL receptors. Lastly, vitamin C raises catabolism levels and clearance LDL.Conclusion: There are increases in HDL levels in the MetS model group receiving ethanol extract VA leaves.